Education and Women within the Framework of the Ideology of Local Media - Martin Kustati; Hetti Waluati Triana; Nelmawarni Nelmawarni (Institut Agama Islam Negeri Imam Bonjol Padang, 2024)
Education in Minangkabau is fundamental in relation to women and their role in all aspects of life, especially because the Minangkabau people, the largest ethnic group in West Sumatra, adhere to a material-lineal kinship system. This article aims to describe education and women represented by local media in West Sumatra. Data was collected using documentation techniques, interviews and Focus Group Discussions (FGDs). Documentation techniques are used to obtain lingual data, while interview and FGD techniques are used to collect data related to the information on the news production process. Data were analyzed by using the Sara Mills framework. The results of the research show that forms of representation of women in mass media can be classified into 13 thematic clusters based on specifications of the substance of the news and the point of view of the writing. The West Sumatra’s mass media represents women more as subjects than as objects. In various forms of reporting, women are represented as independent, warriors and achievers in the field of education. This finding refutes the claim that women are the second class and indicates that West Sumatra media reporting is classified as a gender responsive reporting.